Increasing footprint of climate warming on flash droughts occurrence in Europe. (1st June 2022) - Shah, Jignesh; Hari, Vittal; Rakovec, Oldrich; Markonis, Yannis; Samaniego, Luis; Mishra, Vimal; Hanel, Martin; Hinz, Christoph; Kumar, Rohini
Abstract: Flash droughts are caused by a rapid depletion of soil moisture, and they severely affect vegetation growth and agricultural production. Notwithstanding the growing importance of flash droughts under the warming climate, drivers of flash droughts across the Europe are not well understood. Here we estimate the changes in flash droughts characteristics across Europe using the ERA5 reanalysis dataset for 1950–2019 period. We find a substantial increase in the frequency and spatial extent of flash droughts across Europe (with 79% of the total area) during the growing season with at-least one fourth of domain showing two-fold increase in the recent decades. Increased occurrence of flash drought is largely attributed to frequent occurrence of warmer and drier compound extremes, with a sharp gradient of changes being noticed in Mediterranean and Central European regions. Compound meteorological extremes causing the flash drought events across Europe are pre-dominantly driven by the recent climate warming. With unabated greenhouse gas emissions and current pace of climate warming, Europe is likely to face an increased occurrence of flash droughts, requiring prompt response for effective drought adaptation and management strategies.